Studi Bioakumulasi Timbal (Pb) pada Ikan Bandeng (Chanos chanos Forskall) di Tambak Sekitar Perairan Sungai Buntung, Kabupaten Sidoarjo [ Studies Bioaccumulation of Lead (Pb) in Milkfish (Chanos chanos Forskall) at The Fishponds Around Buntung River, Sidoarjo] - Rr. Juni Triastuti; Singgih Aditama; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Lead (Pb) has been recognized as hazardous metal because it is commonly found as contaminant, interfere the survival of aquatic organisms, and cause bioaccumulation process in aquatic biota at the waters. Bioaccumulation refers to the accumulation of substances in organism that can trough the food chain reaction of aquatic tissue. Bioaccumulation may occur in milkfish cultivated in fishponds around the Buntung river, Sidoarjo, because there are a lot of factories or industrial activities operating and disposing the waste along the river. The purposes of this study are to measure the lead (Pb) content in milkfish at pond around Buntung river, Sidoarjo, and to determine concentration of water and sediment river, water and sediment of fishponds, klekap, and milkfish meat from fishponds, and also to has exceeded specified maximum limit. Design of this study is descriptive study. The samples were collected from 4 stations that located in Buntung river, Sidoarjo, include water and sediment of river, water and sediment of fishponds, klekap, meats and gills from milkfish. Analyze the lead (Pb) content of water, sediment, and biota used Atomic Absorption Spectrophotometry (AAS). The histopathology slide was made by Haematoxylin-Eosin coloration. Cells of controls are the gill filaments at magnification up to 1000 times. The results showed concentration of lead (Pb) in the river water was about 0,018–0,028 ppm, the sediment of river (2,664–3,072 ppm), the water of fishponds (0,000-0,011 ppm), the sediment of fishponds (2,974-3,220 ppm), klekap (0,176-0,192 ppm), and milkfish meat (0,175-0,190 ppm). The lead concentration of each objects have lower than standardization of quality. The injuries found on the gill filaments of milkfish sample histopathologicaly are cell necrosis, rupture of secondary lamella, and congestion.